220k views
2 votes
An equation is shown below: 4(x − 3) − 5(x + 1) = 3 Which statement shows a correct next step in solving the equation? The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication. The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property. The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property. The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication.

User Adaxa
by
5.7k points

2 Answers

4 votes

Answer : The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

User Mithrax
by
5.6k points
2 votes

Answer:

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

Explanation:

An equation is shown below:

4(x − 3) − 5(x + 1) = 3

This equation shows, the equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

The distributive property is when you multiply the sum in the equation and multiply each number or addend in the equation.

User Jarvan
by
6.3k points